THE RELATIONSHIP OF ACHIEVEMENT MOTIVATION AND ACADEMIC PROCRASTINATION OF HIGHSCHOOL STUDENTS - Winy Nila Wisudawati; Aulia Kirana (Universitas Mercu Buana Jakarta, 2022)
To get learning outcomes at school or outside school hours, there is a phenomenon where students feel less motivated by various activities and assignments. Feelings of laziness can encourage students to postpone doing their work, so that assignments pile up. Procrastination is called procrastination (Zimmerman, in Alfina, 2014). Procrastination that often occurs in the academic environment is called academic procrastination (Salomon & Rothbulum, 1984). This phenomenon can affect the learning process until student learning outcomes. Academic procrastination can shape dishonest behavior, because students will be encouraged to look for reasons to not do the assignments or postpone them (Basco, 2010). According to Pintrich and Garcia (in Djiwandono, 2006), the existence of motivation will help students focus on learning. This study aims to determine the relationship between achievement motivation and academic procrastination to highschool students. Participants (N = 130) were highschool students in the age range of 15-18 years, who were selected using non-probability sampling techniques with purposive sampling method. The results obtained showed there is a significant relationship on the variables of achievement motivation and academic procrastination.